Meeting the contraceptive needs of HIV positive adolescent females living in urban townships in Western Cape, South Africa: perspectives of clients and primary health care providers - Olagbuji, Biodun Nelson (University of Cape Town, 2021)
Background: Contraception remains the cornerstone of the global strategy to prevent unintended pregnancy, as well as horizontal and perinatal/postnatal HIV transmission in women living with HIV (WLHIV), including female adolescents living with HIV (ALHIV). Although increased data and research on WLHIV contraception has provided opportunities to strengthen contraception services in HIV programmes, little is known about ALHIV contraceptive behaviours and needs, as well influences on their access to and utilisation of contraceptive services to inform the design of strategies that would enhance optimal contraceptive services in ALHIV programmes. Methods: A mixed-methods design included a cross-sectional study of female ALHIV (n=303) through a questionnaire survey, and semi-structured in-depth interviews with both system- and service delivery-level providers (N=19). Quantitative data were analysed using Stata 15. Quantitative analyses include descriptive statistics and regression modelling, including multinomial and multivariate logistic regressions. Thematic analysis of qualitative data was conducted using Nvivo 11. Quantitative and qualitative data were triangulated in the interpretation of results. Results: Contraceptive prevalence (83.5%) is extremely high among all the female ALHIV and even higher among sexually active female ALHIV (86.8%), and contraceptive prevalence rates are at least 20% higher than the South Africa Demographic and Health Survey (SADHS) rate for the general population of female adolescents or sexually active female adolescents. The rate of unmet need for contraception (23.6%) remains considerable. Contraceptive prevalence is also high among both female with peri/postnatally acquired HIV (pALHIV) and horizontally acquired HIV (hALHIV). The majority of current contraceptive users relied on injectables (60.5%), followed by condoms alone (27.7%), then long-acting reversible contraceptives [LARC](9.1%) and hormonal pills (2.7%). Almost 1 in 5 (18.8%) female ALHIV had an unintended pregnancy. When contraceptive use consistency was restricted to the three months preceding the survey, levels of consistent condom use and dual-method use were 37.9% and 20.6%, respectively. Also, the quantitative data shows multiple barriers and facilitating factors for contraceptive uptake among female ALHIV. Overall, both the quantitative and qualitative data generally found that the receipt of contraceptive provision and use are similar between female pALHIV and hALHIV; however, the quantitative data suggest that pALHIV were more likely to experience unintended pregnancies compared to hALHIV. Though the quantitative data lack information on the particular hormonal method associated with HIV-specific safety concerns, there is evidence suggesting that the concern about HIV-specific hormonal contraceptive-related risks does not impact hormonal contraceptive uptake among ALHIV. Furthermore, adolescent-friendly services (AFS) appear to have been reasonably well-mainstreamed into routine care in the Cape Town context at least, to the extent that standalone youth clinics do not appear to provide significant added value to contraception-related outcomes among female ALHIV. The qualitative data highlighted preponderance of injectable contraception, inconsistent contraceptive use, fears about the intrauterine device (IUD) use, positive and negative provider attitudes to contraceptive services for ALHIV, and provider competency and training, among others. Conclusion: Overall, the thesis supports socioecological-based approaches to contraceptive care for female ALHIV as well as mainstreaming AFS within public sector facilities. Moreover, potential risk-reducing interventions, such as a client-centred approach to contraceptive care, are needed to improve pALHIV's risk of unintended pregnancies.